Thermogenic and metabolic consequences of thyroid hormone treatment in brown and white adipose tissue. Issue 2 (February 1985) - Williams, Christine M.; Ellis, Rodney
Abstract : Male rats were treated with triiodothyronine in the drinking water for 12 days. In vitro rates of isoprenaline stimulated lipolysis were significantly greater in brown but not white adipose tissue. Rates of [ 14 C]glucose incorporation into triacylglycerols were significantly reduced in BAT (brown adipose tissue) and WAT (white adipose tissue) under basal and isoprenaline stimulated conditions, in a second experiment, hyperthyroid animals showed impaired weight gain, despite increased food intake during t9 days' treatment. Energy expenditure on days 5 and 12, and BAT core temperature differences (TBAT – TCORE ) on day 19, were significantly greater than in control animals. Epididymal white fat pad weight was reduced and interscapular brown fat pad weight increased by triiodothyronine treatment.